The global belonging support framework: Enhancing equity and access for international graduate students - Mai, Nhu Tam; Cao, Wenyang; Wang, Yizhen (Journal of International Students, 2025)
This study examines how international graduate students experience institutional support, access, and a sense of belonging within U.S. higher education. Using a constructivist grounded theory approach, we conducted semi-structured interviews with students, alumni, and faculty/staff at a single private research university. Thematic coding and visual analyses (word cloud and quote frequency) revealed three systemic equity barriers: institutional opacity (“Through the Maze”), cultural misalignment (“Lost in Translation”), and fragmented career–immigration guidance (“Dreams on Pause”). In response, we propose the Global Belonging Support Framework (GBSF)—a practice-oriented model comprising four key pillars: proactive advising, peer mentorship and digital community, culturally responsive training, and integrated support for career development and immigration needs. While the study is limited in generalizability, it contributes to the literature by reframing support as a structural challenge rather than an individual adjustment issue. The GBSF offers a transferable design lens for equity-focused reform across higher education contexts.